2021
DOI: 10.1590/2177-6709.26.3.e2119177.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the different debonding strength of metal and ceramic brackets on the degree of enamel microcrack healing

Abstract: Objective: This study aims to determine shear debonding strength of metal and ceramic brackets, and the degree of enamel crack healing. Material and Methods: Extracted human maxillary premolars were flattened on the buccal surface, and randomly separated into five groups (n = 15). In control groups (groups 1 and 2), metal and ceramic brackets were bonded on flat polished enamel, while in experimental groups (groups 3 and 4), metal and ceramic brackets were bonded on the surface with boundary where corner cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…This increased SBS of ceramic brackets is in agreement with previous studies where ceramic brackets had greater bond strengths compared to metal brackets. [9][10][11] . This increased SBS of ceramic brackets may be attributed to the fact that ceramic brackets bond both by micromechanical and chemical bonds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased SBS of ceramic brackets is in agreement with previous studies where ceramic brackets had greater bond strengths compared to metal brackets. [9][10][11] . This increased SBS of ceramic brackets may be attributed to the fact that ceramic brackets bond both by micromechanical and chemical bonds.…”
Section: Discussionmentioning
confidence: 99%
“…7 Bonetti et al studied shear bond strength (SBS) of brackets after scaling with three various angulations of the scaler tip and found that the bond strength was least affected with 45° angulation. 8 The difference in bond strength between ceramic and metal brackets is still debatable with studies showing ceramic brackets to have higher SBS, [9][10][11] while few studies showed higher SBS values with metallic brackets. 12,13 The fracture resistance of ceramic brackets is 20-40 times less than that of metallic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…Although sandblasting on highly translucent zirconia might deteriorate the flexural strength, the bonding ability to resin cement could be enhanced due to the microcracks created during sandblasting and thus, higher shear bond strength could compensate for the negative impacts on the mechanical properties [27]. With regard to tooth bonding, it was suggested that enamel microcrack healing with adhesive resin could prevent crack propagation, leading to increased fracture toughness [48]. A recent study [8] reported that with 25-µm alumina particles, there were no significant changes in Sa (arithmetic mean height) values for all dental zirconia grades.…”
Section: Discussionmentioning
confidence: 99%
“…Reference [27] stated "Within the limitations of this study, even though ceramic brackets required significantly higher debonding force compared to metal brackets, debonding stress was limited to the bonding site and did not affect the surrounding cracks on enamel". However, for ceramic brackets, the value was significantly higher than for metal brackets and is comparatively higher than the value range of previous studies (from 10.4 ± 4.1MPa to 21.67 ± 5.19 MPa14-17).…”
Section: Introductionmentioning
confidence: 90%